PENGARUH LATIHAN PANTULAN DINDING TERHADAP KEMAMPUAN PASSING ATAS BOLA VOLI PADA SISWA PUTRA DI SMAN 1 BLEGA - Priyanto, Edi; Anwar, Khoirul; Handayani, Heni Yuli (JURNAL ILMU KEOLAHRAGAAN, 2024)
In this study is an extracurricular student of SMA Negeri 1 Blega, Learning about the basic passing technique because passing up is one technique that is very simple and easy. Passing over to feed and pass the ball to a friend or team to generate points. So passing this is taught to students extracurricular at SMA Negri 1 Blega and easier to learn passing up because the required energy is not too large so that in a short time it can master. This type of research is a type of pre-experiment research of one groups pretest posttest design. The sample uses 20 extracurricular students. Techniques of collecting data using test techniques. For upper passing ability instrument use passing top measurement test based on AAHPER instrument volunteer skill test theory. Based on the result of research and discussion about the effect of passing exercises wall reflections on the ability passing over students extracurricular SMA Negri 1 Blega. At SMA Negri 1 Blega in the category of both students extracurricular with test result of pretest and posttest normality that the value of 0.268> 0.05 and the value of posttest 0.072> 0.05 and there are homogeneity test results with significant value of 0.276> 0.05 so that the data is homogeneous. And the second using homogeneity test with significant value 0.889 so that the data is homogeneous. The third is using the statistical test or t test, t test results obtained t count value of -5.314 and the value of t table (0,05) (19) equal to 0,95 with significant level 0,00. Therefore t value greater than t table (-9,787 <0,95), it can be concluded that be found influence of reflection of the wall and increase passing up on students extracurricular at SMA Negri 1 Blega